INCREASING DURATION OF FERTILITY IN WOMEN WITH ENDOMETRIOSIS - Fitria Nengsih; Jimmy Yanuar Annas; Reny I'tishom (UNIVERSITAS AIRLANGGA, 2021)
AbstractIntroduction: Infertility is one of the common clinical symptoms in women with endometriosis. Limited ways to diagnose endometriosis, symptoms of endometriosis considered normal and overlap with other diseases that cause delaying treatment that increase the duration of infertility. This study purpose to analyze the differences in duration of infertility to women with endometriosis and without endometriosis. Method: This study is observational analytical research with retrospective case-control designed by looking at medical records in Fertility Clinic Graha Amerta RSUD Dr. Soetomo Surabaya. Total samples in this research are 50 women with infertility, it is divided into 25 people with endometriosis and 25 people without endometriosis. In the medical records, we can see the duration of infertility in each sample. Results: The duration of infertility >3 years occurs in women with and without endometriosis (72% and 80%). In bivariate analysis using the chi-square test, there was no difference that showed increasing duration of infertility (P = 0.508) between women with endometriosis and without endometriosis. Conclusion: There was no differences in the duration of female infertility with endometriosis and without endometriosis